2023
DOI: 10.3390/jcm12113811
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Hangover Frequency and Severity: The Impact of Alcohol Consumption, Mental Resilience, Personality, Lifestyle, Coping and Mood

Joris C. Verster,
Julie A. Donders,
Anne S. Boogaard
et al.

Abstract: Mental resilience is the ability to bounce back from daily life stressors such as divorce or losing a job. Extensive research has demonstrated a negative relationship between mental resilience and alcohol consumption. That is, both the quantity and frequency of alcohol consumption are greater in individuals with lower levels of mental resilience. There has, however, been little scientific attention paid to the relationship between mental resilience and alcohol hangover severity. The objective of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…The findings were not replicated in other studies, which showed no impact on the presence and severity of hangovers of baseline mood and personality (neuroticism [23] or mental resilience [24,25]). Verster discussed the results of an online survey among N = 153 Dutch adults [26]. The participants reported on the hangover they experienced after their heaviest drinking occasion in the period from 15 January to 14 March 2020, i.e., prior to the COVID-19 pandemic.…”
Section: Moodmentioning
confidence: 99%
“…The findings were not replicated in other studies, which showed no impact on the presence and severity of hangovers of baseline mood and personality (neuroticism [23] or mental resilience [24,25]). Verster discussed the results of an online survey among N = 153 Dutch adults [26]. The participants reported on the hangover they experienced after their heaviest drinking occasion in the period from 15 January to 14 March 2020, i.e., prior to the COVID-19 pandemic.…”
Section: Moodmentioning
confidence: 99%